Research progress and application of artificial intelligence in thyroid associated ophthalmopathy - Diao, Jiale; Chen, Xinxin; Shen, Ya; Li, Jian; Chen, Yuqing; He, Linfeng; Chen, Sainan; Mou, Pei; Ma, Xiaoye; Wei, Ruili (Frontiers in Cell and Developmental Biology, 2023)
Thyroid-associated ophthalmopathy (TAO) is a complicated orbitopathy related to dysthyroid, which severely destroys the facial appearance and life quality without medical interference. The diagnosis and management of TAO are extremely intricate, as the number of professional ophthalmologists is limited and inadequate compared with the number of patients. Nowadays, medical applications based on artificial intelligence (AI) algorithms have been developed, which have proved effective in screening many chronic eye diseases. The advanced characteristics of automated AI devices, such as rapidity, portability, and multi-platform compatibility, have led to significant progress in the early diagnosis and elaborate evaluation of these diseases in clinic. This study aimed to provide an overview of recent AI applications in clinical diagnosis, activity and severity grading, and prediction of therapeutic outcomes in TAO. It also discussed the current challenges and future prospects of the development of AI applications in treating TAO.